Tinjauan Tentang Implementasi Corporate Sosial Responsibilty (CSR) Pada Perusahaan - Lestari Wuryanti (Jurnal Riset Akuntansi dan Manajemen Malahayati, 2013)
CSR is a company's commitment to the program as a form of corporate social responsibility. A long-term investment for the comp any for growth and sustainability and the company is no longer seen as a means of cost ( cost center ) but rather as a means of profit ( profit centers ). CSR becomes part of enterprise risk management, nam ely as a social safety valve (social responsibity), due to the well-being and socio-econ omic life of local communities and society at large to be more secure, which will ensure the smooth run ning of the entire production process or activity o f the company and the marketing of the company's prod uction. Concern for the environment that will ensure the smooth process of improving the producti vity of the company, increasing the profitability of the company. Benefits to companies include: Impr ove Corporate Image, Strengthening " Brand " Company, Developing Cooperation with Stakeholders, Differentiating with rival companies, product companies have the opportunity better known by the public. Keywords : CSR , corporate social responsibility